Performance evaluation of a Radio over Fiber (ROF) system subject to the transmitter's limitations for application in broadband networks - Mikroulis, S.; Karabetsos, S.; Pikasis, E.; Nassiopoulos, A. (IEEE transactions on consumer electronics, 2008)
The increasing demand for high data rates in wireless networks indicates radio-over-fiber (RoF) as an excellent candidate for physical layer infrastructure in the development of future broadband communication systems. In this work, a thorough investigation on the performance of an intensity-modulation direct detection (IM-DD) RoF system utilizing orthogonal frequency division multiplexing (OFDM) is performed, emphasizing on the transmitter's impairments, and to what extend the above limitations are compensated by typical demodulation techniques implied in OFDM technology. It is shown that an acceptable performance is depicted up to 5.8 GHz carrier frequency, by a proper adjustment of the laser's current RF amplitude level.